The Use of Word Square Learning Model to Improve Student Learning Outcomes in Theme 6 Lessons in Class III of Elementary School 054938, Langkat Regency - Ambaretno, Dianita Amelia (Lembaga Riset Mutiara Akbar, 2024)
Research is to determine student learning success before using the Word Square learning model for class III students at SD Negeri 054938 Langkat Regency. to determine student learning outcomes using the Word Square learning model for class III students at SD Negeri 054938. This research uses the PTK approach. The results of this research show that observations for the pretest showed that there were 22 students who had not completed it or 88% and 3 students who had completed it or 12%. The success of student learning using the Word Square learning model in cycle I did not meet the KKM standards, where 10 students met the KKM scores, and 15 more students did not meet the KKM. The success of students' learning using the Word Square model in cycle II has met the KKM standards, where 23 students have met the KKM score, and 2 more students have not met the KKM score. From the calculation results, the first cycle average was 67.2 and the second cycle average was 85.6. So that student learning success is obtained at 92%. This means that class III of SD Negeri 054938 Langkat Regency experienced an increase in learning success to the high category because it was more than 85%.